Effect of Ausforming on Retained Austenite After Continuous Cooling Transformation in a Medium-Carbon High Strength Steel - Liu,Man (2020)
Abstract The effects of deformation on transformation kinetics during continuous cooling and microstructure evolution of a medium carbon high strength steel were investigated by metallographic method, dilatometry and X-ray diffraction etc. The results show that ausforming accelerated the ferrite and martensite transformation, but significantly retarded the bainite transformation. In addition, the amount of retained austenite decreased first and then increased, while the carbon content in retained austenite increased with the accumulation of strain. The change trend of the average dislocation density in martensite with strain showed the opposite trend as that of the amount of retained austenite. Moreover, the martensite laths were refined by ausforming. The work provides the theoretical reference for the design of parameters of thermalmechanical controlled process (TMCP) in the production of medium-carbon high strength steels.